The contingency effects of supply chain integration on management control system design and operational performance of hospitals in Ghana - Nartey, E.; Aboagye-Otchere, F.K.; Simpson, S.N.Y. (Journal of Accounting in Emerging Economies, 2020)
Purpose – This paper extends prior contingency-based management accounting research by building and empirically testing a theoretical model of contingency effects of supply chain integration (SCI) on the dimensions of management control system (MCS) and supply chain operational performance (SCOP) of hospitals in Ghana. Design/methodology/approach – The paper uses factorial and structural path analysis of survey responses collected from 237 hospital accountants to model these relationships. Findings – The results show that under strong SCI, the association between the MCS dimensions and hospital operational performance namely, cost effectiveness, flexibility and quality will be strengthened. In other words, the installation of MCS is more likely to provide a broad range of performance benefits for hospitals that align the four dimensions of the MCS with the dimensions of SCI (internal and external). Research limitations/implications –Alimitation of this study would be its limited scope, as it focused only on hospitals in one developing country. Therefore, the results as indicated here may have limited generalizability to other industries and countries. Practical implications – We theorize that using optimal amounts of the MCS, a high level of SCI is likely to reduce supply chain (SC) cost, improve speed, flexibility and quality of the SC among healthcare institutions in Ghana. Also, based on the direct impact on performance exhibited by the MCS dimensions, effective implementation of SCI decisions requires the use of optimal amounts of MCS for high performance. Originality/value – The paper contributes to contingency-based management accounting research and provides theory-driven and empirically proven explanations for hospital managers in recognizing the importance of aligning the dimensions of SCI and MCS.
Research Article
Keywords: Hospitals; Supply chain integration; Management control systems; Supply chain operational performance